The role of thermodynamics and kinetics in rubber–bitumen systems: a theoretical overview. Issue 14 (6th December 2021) - Wang, Haopeng; Apostolidis, Panos; Zhu, Jiqing; Liu, Xueyan; Skarpas, Athanasios; Erkens, Sandra
ABSTRACT: Waste tire rubber has been incorporated into asphalt modification for decades due to its various benefits. There are two main mechanisms during bitumen–rubber interaction: rubber swelling and chemical degradation. This study surveys these two processes from the viewpoint of polymer science. The kinetics of rubber dissolution and thermodynamics of rubber swelling are discussed to provide a fundamental understanding of the interaction process and to demonstrate how optimisation of material selection and processing procedures can lead to the desired binder properties. Factors including the interaction conditions and raw material characteristics are analysed based on the previous theories and compared with experimental results.